The History of Batik and The Development of Kampung Batik Kauman as a Local to International Tourism Destination - Pramesi Lokaprasidha (Journal of Tourism and Creativity, 2019)
Abstract The history of batik is closely related to the rise of Majapahit Kingdoms and the succeeding kingdoms. It has been widely believed that according to some written references batik that we know today, using wax as the resist agent to draw the motifs, was first developed in MataramKingdom reign, continued by the age of the Kingdom of Surakarta (Solo) and Jogjakarta. The golden age of batik producing was toward the end of the 18th century and the beginning of the 20th century.The origin of batik dates as early as the period when our ancestor in the 17th century attempted to write and paint on the palm frond. During that age the motif was redominantly local flora and fauna, which subsequently developed into ornaments influenced by the Hindu religion, such as clouds, temple stone relief, shadow puppet characters and other intriguing objects. The integration of painting motifs and decorative clothes eventually led to the rise of hand – drawn batik as we know it today. In addition tobatik products, Kampung Batik Kauman also surrounded by a lot of historic building, such as joglo (the old type of traditional house), pyramid, colonial, and the combination of Javanese and colonial architecture. Keywords: Batik, Kampung Batik Kauman, Tourism Destination